Investigation of the potential mechanisms behind dysfunctional labour with maternal obesity - Mustikaningrum, Fitriana (2022)
The prevalence of obesity among pregnant women in Europe varies, ranging from 8 to 25% where the UK is currently ranked top with 25% of pregnant women classified obese. Public Health Scotland identified that 50% of women booking antenatal care between January 2018 and March 2019 were overweight and obese with 30% of the pregnant women delivering their baby by caesarean section. The mechanism underpinning prolonged and dysfunctional labour with maternal obesity is currently unresolved. Maternal obesity is associated with increased lipid accumulation in the placenta and myometrium that causes uterine myocytes to be less responsive to oxytocin and PGF2α. Recently, our research group established that feeding a High-Fat, High-Cholesterol (HFHC) diet to induce obesity in rats increases omega-9 and decreases both omega-3 and omega-6 fatty acids in the plasma and liver. However, only total omega-3 PUFAs decreased significantly in the uterus which exhibited unsynchronised myometrial contractions at term labour. Decreasing omega-3 in the uterus after chronic exposure to the HFHC diet suggests that the adverse effects of obesity on myometrial contractile activity could be improved by increasing omega-3 status. Thus, a key aim of this research was to investigate further the potential mechanism(s) behind prolonged and dysfunctional labour associated with maternal obesity. To achieve this, pregnant Wistar rats were fed different diets. The first experiment was setup to try and determine whether poor contractile function of the uterus after HFHC feeding in the rat is caused by increased lipid accumulation within the myometrium. Rats were fed either a control or HFHC diet and then culled for tissue collection either at term or during parturition. The aim was to evaluate the effect of the HFHC diet on the number of vacuoles and vacuole area in the uterus as an indirect representation of lipid accumulation. Furthermore, this study also investigated the effect of different diets on the percentage of fatty acids within the plasma, liver and the uterus and to determine whether there was any correlation between the proportion of fatty acids within the uterus (EPA, DHA, AA and OA) and prostaglandin synthesis. The quantification of plasma concentrations of PGF2α and PGE2 were determined by ELISA kit ( Abcam), while gas chromatography-FID was used to determine the fatty acid levels in the plasma, liver and uterus. Two-way ANOVA was used to analyse the relationship between diet and time of delivery (Term or Labour) on the number of vacuole and mean area of vacuole, while one-way ANOVA was used for analysing the effect of HFHC diet on fatty acid proportion in plasma, liver and uterus. If significantly different, the Post hoc LSD statistic test was used at the P<0.05 level. The correlation of fatty acids within the uterus and plasma type 2 prostaglandins type were analysed by Spearman statistic test. The results of the study were that exposure to a HFHC diet significantly alters lipid accumulation in the uterus, alters plasma, liver and uterine fatty acid proportions that correlated with plasma type 2 prostaglandins. The uterus from rats fed a HFHC diet throughout pregnancy significantly increased the mean number and mean area of vacuoles compared to the control group. The HFHC group had twice the number of vacuoles compared to controls. The HFHC diet also significantly increased the proportion of saturated fatty acids and OA, but decreased the proportion of omega-3 and omega-6 in the plasma and liver, meanwhile, only omega-3 was significantly decreased in the uterus. Interestingly, changing diet from a HFHC diet to control at conception and fed throughout pregnancy increased the percentage of omega-3 in the uterus (P< 0.05). Since a high fat diet affects uterine fatty acid proportions, the next study aimed to investigate whether a high fat diet alters the proportion of fatty acids in the placenta as well as protein expression of PPARs and aromatase. PPARs are nuclear receptor proteins that has a function as transcription factors regulating the expression of genes associated with inflammation and lipid homeostasis. Moreover, the placenta is an important organ for the synthesis of steroid hormones including progesterone and oestrogen. As our research group established that the HFHC diet increased progesterone production at term compared to controls it suggests maternal obesity may cause prolonged and dysfunctional labour via altered steroid synthesis. Aromatase is one of the enzymes that are essential for oestrogen synthesis, but many studies reported that it is inhibited by PPAR γ. Therefore, the hypothesis to test was that HFHC diet would affect the proportion of fatty acids within the plasma and placenta. This study also determined whether a HFHC diet increase protein expression of PPARs but decreased protein expression of aromatase in the placenta. Western blotting was used to analyse protein expression of PPARs and aromatase in the placenta, while the proportion of fatty acid in the placenta used the same method as that in the first chapter of the study. One Way ANOVA was used to analyse the different proportions of fatty acids and protein expression of PPAR between the HFHC control groups, followed by the LSD test if it significant differences were identified at the P<0.05 level. The result of this study was that exposure to the HFHC diet decreased the saturated fatty acid proportion but significantly increased DGLA compared to the control group (P<0.05). Moreover, rats fed the HFHC diet had significantly higher protein expression of PPAR γ compared to the lean control group (P=0.01). As we had identified decreased omega-3 status in the uterus after chronic exposure to the HFHC diet it suggested that the adverse effects of obesity on myometrial contractile activity could be improved by increasing omega-3 status. Moreover, our research group established that a HFHC decreased protein expression of key contractile associated protein (CAPs) such as CX-43 and OXTR. Fatty acids, especially omega-3 PUFA’s could enhance the membrane fluidity which potentially increase the coupling efficiency of G-Protein such as free fatty acid receptor (FFAR) that has the potential to modify the signalling and mRNA stability of connexin and transcription activity of the connexin gene. Furthermore, fatty acids could be taken up by fatty acid-binding protein (FABP) in coordination with CD36 receptor and transport them from membrane to the cytoplasm altering function of the CAPs in the cell. Therefore, the third chapter of the study was to investigate the effect of different ratios of the omega-3 PUFA ALA and omega -6 PUFA LA at two different fat levels on uterine protein expression of CAPs (CX-43, Cav-1, COX-2), OXT, PCX-43) and PPARs (PPAR α,PPAR γ and PPAR δ). For this experiment pregnant rats were fed different ratios of omega-3 and omega-6 followed at two fat levels ; high omega-3 and high fat diet (1:1.5 36%), high omega-3 and low fat diet (1:1.5 18%), high omega-6 and high fat (9:1 36%), high omega-6 and low fat (9:1 18%). Western blotting was used to determine protein expression of CAPs and PPARs. Two-Way ANOVA followed by LSD determined whether there was a relationship between diet and level of fat on protein expression of CAPs and PPARs. Exposure to the high omega-3 PUFA diet significantly increased protein expression of CX-43 and Cav-1 (P<0.05). In contrast, the high omega-3 diet significantly increased COX-2 protein expression but only if fed at the higher 36% fat level (P=0.02). Statistical analysis identified an interaction between diet and the level of fat on PPAR α expression within the uterus (P=0.02) where the high LA high fat group (9:1 36%) had the highest expression of PPAR α in the uterus. The finding that improved omega-3 PUFA status increases uterine protein expression of CX-43, Cav-1 and COX-2 suggests that there is potential to improve myometrial contractile activity during parturition in obese pregnant women. The OA also has the potential to alter myometrial contractions since previous results identified that the HFHC diet significantly increases OA levels in the liver and plasma. Uterine and plasma levels of PGF2∝ have also been shown to have a positive correlation with OA levels in the uterus. There is evidence to suggest that OA might contribute to increased systolic calcium-free concentrations and activate Ca2+ dependent PKC isoenzymes to promote redistribution of protein kinase C (PKC) from the cytosol to the plasma and possibly alter the signaling pathways associated with myometrial contraction such as gap junction, prostaglandin type 2 receptor and MLCK. Thus, the fourth chapter of the study aimed to investigate the effect of OA on myometrial contractile activity in an ex-vivo organ bath study. Myometrial strips from term-labour pregnant rats fed a control chow diet were used in this study. Strips of myometrium were left to equilibrate for 30 to 40 minutes in an organ bath. Baseline recording of 15 minutes spontaneous uterine contractility was determined before accumulative response to increasing doses of OA, the PKC inhibitor (Go6983) or accumulation of OA in combination with either the PKC activator (PMA) or PKC inhibitor (Go6983) were recorded. The myometrial contractile activity was extracted from Lab Chart Reader software and the ordinary fit least square analysis was used to determine the correlation between OA dose and the myometrial contractile parameters and the correlation between Go6983 exposure with myometrial contractile activity. Dose-response curves were used to analyse the concentration of OA or Go6983 that inhibit 50% of myometrial contractile force or stimulate 50% of contractile (EC50) force. The Repeat Measured ANOVA statistical test was used to determine the effect of myometrial response to PMA when exposed to increasing concentrations of OA and the effect of Go6983 in combination with increasing concentrations of OA and PMA on myometrial contractile activity. The result of this experiment was that exposure to OA leads to poorly synchronized myometrial contractions and decreased frequency of contractions but increased mean and peak amplitude and time of the peak in a dose dependent manner. However, PMA in combination with increased accumulation of OA did not alter myometrial contractile activity. Meanwhile, administration of Go6983 in combination with PMA and OA had the reverse effect of myometrial contractile activity which shows increased frequency but decreased peak of amplitude (P<0.05). Furthermore, the individual effect of PKC inhibitor Go6983 towards uterine contractions showed a significant decrease in the peak amplitude and frequency of uterine contractions (P<0.05). The poorly synchronized and decreased frequency of myometrial contractions after OA administration and the reverse effect of myometrial contraction after Go6983 administration suggests that OA might alter myometrial contraction through PKC activation. In conclusion, besides obesity itself, fat and PUFA diets, especially LA and ALA have the ability to alter myometrial contractile activity through altered protein expression of CAPs and PPARs. Improving omega-3 status through dietary intervention is a potential treatment to prevent dysfunctional labour with maternal obesity, and acts by increasing protein expression of the CAPs such as CX-43, Cav-1 and COX-2. Furthermore, evidence suggests that OA increased the amplitude of contraction but otherwise decreased their frequency. In addition, OA induced unsynchronized myometrial contractions during parturition via PKC which might be detrimental to pregnant women.